A succinct medical safety: periodic safety update reports - Krishnamurthy, Arun Chander Yadav; Dhanasekaran, Jayasudha; Natarajan, Anusha (International Journal of Basic & Clinical Pharmacology, 2017)
In the rapidly developing era of advanced of medical sciences, pharmacovigilance plays an important role to put necessary brakes and help the medical fraternity to prescribe in a safe manner. Unanimously PSUR contributes in an essential way to regulate the drug marketing agencies to make sure that biological products which are marketed do not harm the general population by its adverse drug reactions. As we all know that the regulatory agencies like EMA, US FDA, CDSCO etc. are very stringent in approving the drugs, they have framed several rules and imposed strict timelines for reporting the necessary documents pertaining to drugs. Inevitably several new drugs like immunomodulators, anticancer drugs are on the raise which further adds a huge responsibility on the regulatory agencies regarding the risk and benefits of such biological products. Thus, the regulatory agencies have added several new implementation and amendments in the existing rules for the marketing of new drugs as well as already prevailing drugs. Hence, it is of paramount importance for the drug companies to follow the guidelines and abide by the rules of regulatory agencies for the benefit of mankind. However, several factors can impede the process of PSUR like improper data retrieval, inadequate training of resource personnel concerned with the development of PSUR. To overcome such difficulties, the field of advanced technology extended its arms for the regulatory authorities to implement electronic documentation and databases for the development of PSURs. In spite of all these efforts several challenges are to be met in the future in the field of pharmacovigilance. In this review several aspects of PSUR in different countries, necessary processes and format in which it needs to be submitted, pitfalls and ways to overcome such situations have been discussed in brief. Therefore, it is the collective responsibility of both Regulatory agencies and the drug companies to ensure a good quality PSUR is produced with its benefits outweighing the risk of the drug for the suffering human population.